مساهمة بيداغوجيا المشروع بالسنة الرابعة من التعليم الابتدائي في معالجة صعوبات الكتابة تحليل نماذج من مدارس الوادي - حنكة, عطا الله, فتيحة ساسية (Univercty of Eloued, 2020)
يكتدي ىحا البحث أىمية بالغة كهنو يتطخق إلى مهضهع " مداهمة بيداغهجيا المذروع بالدنة الاربعة من التعليم الابتدائي في معالجة صعهبات الكتابة - تحليل نماذج من مدارس الهادي-" فيحه الجارسة تحاول معالجة الرعهبات الكتابية التي يعاني منيا متعممي الدنة الاخبعة ابتجائي من خلال بيجاغهجيا المذخوع، والتي ىي مقاربة تخبهية ججيجة استطاع المتعممين من خلال إنجازىم لممذخوع البيجاغهجي بنهعيو الفخدي والجماعي معالجة وىحا ما لاحعناه عنج تحميمنا لممذاريع التخبهية الفخدية والجماعية، إذا ،الرعهبات الكتابية اشتمل الإنتاج الكتابي عمى الكثيخ من الرعهبات الإملائية - الخطية- التعبيخية، مقارنة بإنجازىم لممذخوع والحي قج ساىم في تنمية ممكة الكتابة من خلال حدن انتقاء الألفاظ المناسبة لممعاني وكحا التاخكيب والتعابيخ التي تخجم مهضهع المذخوع، وىحا الأخيخ لو سمات عممية دفعت المتعمم إلى المبادرة وحثتو عمى البحث والتفاعل مع الآخخين ساىمت بذكل كبيخ في تنمية القجارت العقمية وتجاوز بعض ىحه الرعهبات وجعمت منو متجنبا قجر الإمكان الهقهع في أخطاء، ىحا كمو جعل من بيجاغهجيا المذخوع بيجاغهجيا فعالة تيجف نحه معالجة الرعهبات الكتابية وتحقيق كفاءة المكتهب التي تختمف من مذخوع لأخخ ومن متعمم لأخخ لأن أساسيا المذخوع الحي ينجده المتعمم ليدتطيع فيو تهظيف مكتدباتو ودمجيا. This research is of great importance as it deals with the subject of “the contribution of the project's pedagogy to the fourth year of primary education in addressing writing difficulties- analyzing models from valley schools -” as this study attempts to address the writing difficulties that the fourth year primary school learners suffer from through the project’s pedagogy, which is A new educational approach, through the completion of the pedagogical project in its individual and group types, the learners were able to address the writing difficulties, and this is what we noticed when we analyzed the individual and group educational projects, if the written production included many spelling - written - expressive difficulties, compared to their completion of the project, which contributed to the development of Writing by properly selecting the appropriate words for the meanings as well as the compositions and expressions that serve the subject of the project, and the latter has scientific features that prompted the learner to take the initiative and urged him to research and interact with others that greatly contributed to the development of mental abilities and overcoming some of these difficulties and made him avoid as much as possible falling into mistakes All this made the project's pedagogy an effective pedagogy aimed at addressing and investigating writing difficulties The competency of the written work that differs from one project to another and from one learner to another because it is based on the project that the learner accomplishes in order to be able to employ and integrate his gains.
Keywords: البيداغوجيا الكتابة المشروع صعوبات التعلم صعوبات الكتابة .; pedagogy - project - writing - learning difficulties - writing difficulties.